Encephalic and Spinal Subdural Empyema on the Skull of a Dog Secondary to a Puncture Wound - Rauber, Júlia Silva; Wrzesinski, Mathias Reginatto; Chaves, Julya Nathalya Felix; Sekita, Amanda Miwa Takamori; Oliveira, Miguel Dewes; Kommers, Glaucia Denise; Beckmann, Diego Vilibaldo; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2024)
Background: Traumatic brain injury (TBI) is an important cause of morbidity and mortality in humans and animals. Among the causes in dogs and cats, bite wounds stand out. A bite to the skull can cause wounds with direct inoculation of pathological agents into the central nervous system (CNS), which can trigger an infectious process. The objective of this report was to describe a case of subdural empyema in the brain and spinal cord of a dog secondary to a puncture wound to the skull caused by a bite and to report the late neurological complications. Case: A 11-year-old neutered male Poodle dog was referred to the Veterinary Neurology and Neurosurgery Service (VNNS) of the University Veterinary Hospital (UVH) with a history of fighting with another dog 5 days before. According to the owner, shortly after the attack, the dog became temporarily apathetic and, 12 h after the trauma, he appeared normal with no clinical or neurological signs. However, 5 days after the trauma, the dog began to have difficulty walking with all 4 limbs and was sent to VNNS. On physical examination, a puncture wound was observed, with purulent secretion on the skin over the frontal bone region. He did not present any brain signs based on the reported history or the clinical and neurological evaluation of the patient. Based on the neurological examination, the suspected site of injury was the cervical segment of the spinal cord (C1-C5), initially unrelated to the skull injury. The differential diagnosis included intervertebral disc extrusion, vertebral fracture and/or dislocation, infectious disease, immune-mediated inflammatory disease and neoplasms. It was decided to hospitalize the animal for additional examinations and treatment. During this period, the wound was shaved and cleaned and fluid therapy and antibiotic therapy were instituted. After 12 h of treatment, the patient's clinical condition worsened and died. At necropsy, perforation and comminuted fracture of the frontal bone were observed, hairs inserted into the cranial perforation, penetrating the brain parenchyma of the right frontal cortex. There was purulent, turbid exudate, invading the cranioencephalic cavity, lateral ventricles and extending to the subdural space of the cervical spinal cord. In the cross-section of the brain, an irregular and friable area was observed, close to the cortical meningeal surface, reaching the lateral (right) ventricle, from which purulent exudate was draining. There was also purulent exudate and hemorrhage surrounding the brain stem and covering the cervical portion of the spinal cord. Discussion: In this case, at the time of consultation, the neurological signs presented were compatible with a lesion in the cervical segment of the spinal cord (C1-C5), with no evidence of brain signs, both in the observational assessment and in neurological tests. However, after necropsy, the involvement of supraspinal structures (cerebral cortex, brainstem and cerebellum) could also be observed. Another important point in this case was the evolution of neurological signs that began 5 days after the trauma, changing the suspicion of the location and diseases without a possible relationship with the initial trauma to the skull. Therefore, the case has the clinical relevance of alerting veterinarians about the possible late neurological complications caused by subdural empyema and demonstrating that the findings in the neurological examination may not be compatible with the initial site of the injury. Furthermore, the authors emphasize the early approach to any bite wound in the skull region, even if there are no brain neurological signs, in order to investigate the extent of the injury and perform debridement of the affected tissues associated with abundant irrigation (dilution) of the wound with saline solution Keywords: traumatic brain injury, infection, dog bite. Título: Empiema subdural encefálico e espinhal no crânio de um cão secundário a uma ferida punctória Descritores: trauma cranioencefálico, infecção, mordedura de cães.